2018
DOI: 10.1155/2018/1923606
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Cerium Oxide Nanoparticles on Opportunistic Microorganisms: A Systematic Review

Abstract: An evaluation of studies of biologically active nanoparticles provides guidance for the synthesis of nanoparticles with the goal of developing new antibiotics/antifungals to combat microbial resistance. This review article focuses on the physicochemical properties of cerium oxide nanoparticles (CeNPs) with antimicrobial activity. Method. This systematic review followed the Guidelines for Transparent Reporting of Systematic Reviews and Meta-Analyses. Results. Studies have confirmed the antimicrobial activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 33 publications
7
73
0
Order By: Relevance
“…Christiano et al revealed that CeO2-NPs showed an antibacterial effect on SM when incorporated in 10% concentration with dental composite [31] . Also, CeO2-NPs revealed less antibacterial activity against gram positive bacteria as SM, which difficult to be penetrated with CeO2-NPs [22] . This fact could explain the lower antibacterial activity of CeO2-NPs in relation to ZnO-NPs, which have a higher antibacterial effect against gram positive bacteria [32,33] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Christiano et al revealed that CeO2-NPs showed an antibacterial effect on SM when incorporated in 10% concentration with dental composite [31] . Also, CeO2-NPs revealed less antibacterial activity against gram positive bacteria as SM, which difficult to be penetrated with CeO2-NPs [22] . This fact could explain the lower antibacterial activity of CeO2-NPs in relation to ZnO-NPs, which have a higher antibacterial effect against gram positive bacteria [32,33] .…”
Section: Discussionmentioning
confidence: 96%
“…Among the metal oxides, the Nano particulate cerium oxide (CeO2-NPs) which belongs to lanthanide series and is a rare earth metal oxide, with antibacterial properties against many types of bacteria [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, green chemistry methods using extracts from plants, fruits, and fungi have also attracted increasing attention recently due to their environment-friendliness, cost-effectiveness and scalability for industrial production. Different synthesis methods and correlated toxicities are summarized in Table 1 [60,61]. As mentioned above, a lower Ce(III)/Ce(IV) ratio is correlated with higher anti-cancer and anti-bacteria efficiency.…”
Section: Synthesis Methodologymentioning
confidence: 99%
“…FTIR spectra were analyzed and illustrated for functional groups analysis of CeO 2 NPs (figure 4). CeO 2 nanostructures by Aspergillus terreus exhibited peaks at 468 cm −1 , 550 cm −1 and 833.5 cm −1 which shows the Ce-O stretch [23,24]. The bands at 2432 and 3425 cm −1 correspond to the vibrational bending of H-O-H and O-H bonds [25,26].…”
Section: Ftir Of Myco-synthesized Ceo 2 Npsmentioning
confidence: 98%
“…Nanostructures might affect the cell by attacking the cell wall structures and permeabilize into the cell. They inhibit the growth or kill the cells by inhibition of certain pathways such as RNA or protein synthesis inhibition, metabolic pathways inhibition and synthesis of cell wall structures inhibition [23]. Another action of mechanism could be the production of reactive oxygen species (ROS) due to the electrostatic interaction between nanostructures and cell wall of Candida albicans [28] (figure 9).…”
Section: Assessment Of Anti-fungal Activity Of Ceo 2 Npsmentioning
confidence: 99%